Analisis Pengaruh Motivasi dan Disiplin Belajar Pada Pembelajaran Daring di Masa Pandemi Covid-19 - Iqbal Muhammad Syaifullah; Riswanti Rini; Ujang Efendi; Lilik Sabdaningtyas (JURNAL INOVATIF ILMU PENDIDIKAN, 2021)
The objective of this research was to analyze the effect of learning motivation on learning outcomes, the influence of learning discipline on learning outcomes, and the influence of motivation and learning discipline on learning outcomes during online learning. This research was a quantitative research with ex post facto method. The population of this research amounted to 136 students. The sampling technique used was probability sampling using a simple random sampling technique with the outcomes of 58 students. The data collection technique used was a questionnaire to collect data on student answers and documentation in order to obtain data on learning outcomes. The data analysis techniques used was multiple linear regression test. The outcomes of this research indicated that there was an influence between learning motivation on learning outcomes of 62.7%, learning discipline on learning outcomes of 37.3%, and simultaneously learning motivation and learning discipline on mathematics learning outcomes of 65.6%. The conclusion of this study shows that there is an influence between learning motivation and learning outcomes, learning discipline and learning outcomes as well as learning motivation and learning discipline on mathematics learning outcomes in fourth grade students.Kewords: motivation, discipline, learning outcomes, mathematics for elementary schoolDOI: http://dx.doi.org/10.23960/jiip.v3i1.23043